The Economics of Affirmative Action - Jain, Harish C. (Relations industrielles / Industrial Relations, 2005)
The article reviews the book, "The Economics of Affirmative Action," edited by Harry J. Holzer and David Neumark.
Keywords: Affirmative action; Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Economic theory; Essays; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z